Corelation beetwen fine motor development in children to their social cognitive abilities - Agum Adi Jatmiko (Universitas Pendidikan Indonesia, 2022)
The age of children is one of the crucial periods in the development of a person's life. Development at this time also requires guidance and supervision from the parents / caregivers of the child. Children will also be faced with challenges to be able to socialize and become part of a social group. The social abilities of a child also require adaptation to the social environment they live in, each child must have different social skills and different adaptability. At this time, there are still many parents who think motor development is only able to provide development to the cognitive aspects of children, in fact this is not entirely wrong. It is a good initiative too, if the optimization of children's motor skills is directed at the development of other abilities. Therefore, the existence of proper guidance and supervision will be able to interpret children to manifest themselves completely in a social environment.